Employee Development Strategy in Improving Organizational Performance - Krisnahadi, Tama; Putri, Hilda Faradila; Lukitasari, Diah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine employee development strategies in improving organizational performance at the Bima Regency NTB Communication, Information and Statistics Service office. The research method used in this research is qualitative research with a description approach. The results of this research indicate that the implementation of employee development strategies in improving organizational performance at the DISKOMINFOTIK office (Department of Communications, Informatics and Statistics) Bima Regency, NTB has gone well, marked by an increase in technical competence through information technology-based training, development of non-technical skills such as leadership and communication, as well as preparing a clear and structured career development path. Apart from that, efforts to improve employee welfare and reward systems are also important components in increasing work motivation and productivity. Regular evaluation and adjustments to the implementation of this strategy are carried out to ensure continuous performance improvement. It is hoped that the results of this research can make a significant contribution to operational effectiveness and achievement of the strategic objectives of DISKOMINFOTIK Bima Regency.